2018
DOI: 10.1039/c8mt00219c
|View full text |Cite
|
Sign up to set email alerts
|

Is copper a new target to counteract the progression of chronic diseases?

Abstract: In this review, we highlight the importance of a Cu imbalance in the pathogenesis of several chronic inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 94 publications
0
35
0
Order By: Relevance
“…Copper levels are tightly regulated, and its imbalance can have implications on the development and progression of both chronic and inflammatory diseases (including metabolic, cardiovascular, and neurodegenerative diseases). It can also predispose to malignant processes [68]. A deficit in copper levels can cause impaired levels of energy, abnormal glucose and cholesterol metabolism, increased oxidative damage, and altered function and structure of circulating blood and immune cells [69,70].…”
Section: Coppermentioning
confidence: 99%
“…Copper levels are tightly regulated, and its imbalance can have implications on the development and progression of both chronic and inflammatory diseases (including metabolic, cardiovascular, and neurodegenerative diseases). It can also predispose to malignant processes [68]. A deficit in copper levels can cause impaired levels of energy, abnormal glucose and cholesterol metabolism, increased oxidative damage, and altered function and structure of circulating blood and immune cells [69,70].…”
Section: Coppermentioning
confidence: 99%
“…Copper (Cu) participates in the production of energy in the mitochondria and functions as a cofactor to superoxide dismutase (SOD) found in the cytosol and intracellular space. Over the years, copper imbalances have been linked to chronic inflammatory diseases [179].…”
Section: Influence Of Antioxidants In Diabetic Retinopathymentioning
confidence: 99%
“…The presence of a proinflammatory milieu in the airway is an important characteristic of a variety of chronic pulmonary diseases, such as COPD and asthma, and inflammation plays critical roles in the development of these diseases 15–18 . Although some studies have suggested that inflammatory responses influence copper homeostasis in cells, 19–22 the definitive relationship between inflammation and copper homeostasis remains unclear. Environmental copper, which typically exists in the cupric state, must be firstly reduced to a cuprous state by membrane‐bound metalloreductases 20,23 .…”
Section: Introductionmentioning
confidence: 99%